1973
DOI: 10.1039/cs9730200475
|View full text |Cite
|
Sign up to set email alerts
|

The Brønsted relation – recent developments

Abstract: This is the range over which dG* is a single-valued function of dG" and therefore the range

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
112
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(120 citation statements)
references
References 1 publication
8
112
0
Order By: Relevance
“…Alternatively we may use the best available pKBH+ values for the esters (see Calculations) and see how well the data obey the Marcus equation for mechanism [13]. When the data are plotted in this way, the points fall in reasonable accord with eq.…”
Section: I Imentioning
confidence: 55%
See 3 more Smart Citations
“…Alternatively we may use the best available pKBH+ values for the esters (see Calculations) and see how well the data obey the Marcus equation for mechanism [13]. When the data are plotted in this way, the points fall in reasonable accord with eq.…”
Section: I Imentioning
confidence: 55%
“…The difficulty with process [13] was that the best available values for the pKBH+ values of carbonyl compounds led to some points falling in impossible regions, corresponding to rate constants exceeding the relaxation rate for water (1); this was not compelling because there is considerable uncertainty concerning the true pKBH+ values for simple carbony1 compounds, and recent values for acetone have varied from -2.72 (16) to -5.37 (17). Only for the more negative values of the pKBH+ for acetone and other simple carbonyl compounds do the points fall in forbidden regions.…”
Section: I Imentioning
confidence: 99%
See 2 more Smart Citations
“…Such mechanisms have been shown to be important in exchange reactions that can be followed by nrnr, and in carbinolamine forming processes. As I stated above, my examination of the E2 reaction, combined with a common organic prejudice that proton transfer along a preformed hydrogen bond should be very easy (24,42,43,102,(105)(106)(107), led me to expect a small intrinsic barrier for "fast" proton transfers. ow ever examination of the classic data from Eigen (108) on such proton transfers, interpreted in terms of the classic Eigen mechanism, with a chemical step preceded and followed by diffusional steps, showed that application of Marcus theory to the chemical step required a barrier of 4-5 kcallmol.…”
Section: Conjecture 2: Multidimensional Marcusmentioning
confidence: 99%